Enhancing the targeted and untargeted analysis of honey by vacuum-assisted SPME-GC × GC-MS. A green, practical, and highly informative approach - Damien Eggermont; Francesca Pardi; Giorgia Purcaro (Green Analytical Chemistry)
The use of vacuum-assisted headspace (Vac-HS) coupled with solid-phase microextraction (SPME) is a technique that has been recently proven to be highly beneficial for enhancing the extraction of semi-volatile in shorter time and milder temperatures. This technique indeed increases the extraction kinetics by reducing the mass transfer resistance at the interface between the sample and headspace. In this work, we explored the use of Vac-HS coupled with comprehensive two-dimensional gas chromatography coupled with mass spectrometry to simultaneously determine 5-hydroxymethylfurfural (a semi-volatile processing marker in honey) and the entire volatile profile, which is recognized as a highly informative fingerprint of the geographical and botanical authenticity of honey. The use of Vac-HS-SPME has been optimized using an experimental design and compared to the atmospheric pressure extraction. Considering both 5-HMF and the entire volatile profile, an overall 10-fold higher signal was obtained using Vac-HS-SPME compared to simple HS-SPME. The absolute quantification of 5-hydroxymethylfurfural was fully validated, obtaining a limit of quantification of about 5 µg/g, largely below the lowest required limit for the presence of this compound in honey (i.e., 15 µg/g). The results obtained from a series of commercially available honey were compared with those obtained using the official high-performance liquid chromatography-UV method, obtaining comparable results but through a greener and more practical method. The overall volatile profile obtained by Vac-HS-SPME showed a significant increase in the response of the less volatile compounds, reaching up to a 90-fold increment compared to HS-SPME.